The effect of national economic policy inconsistencies on the general citizens in Harare Central Business District and the economy of Zimbabwe - Mandeya, Edward (Midlands State University, 2017)
A number of national economic policy inconsistencies have occurred in Zimbabwe since the year 2010. This study was carried out to assess the effect of national economic policy deficiencies on the standard of living of ordinary citizens in Harare Central Business District and the economy of Zimbabwe. The researcher applied the pragmatism philosophy and mixed methods approach whereby a combination of qualitative and quantitative data was collected using questionnaires and interviews. Statistical Package for Social Sciences (SPSS) software was used to organise and analyse raw data gathered from participants. It was found that inconsistent national economic policy leads to macro-economic instability, unemployment, shortage of residential accommodation, reduced human welfare, inefficient service delivery, unclear property rights and widening of the gap between rich and poor people. This was caused by the following factors; lack of citizens engagement, poor policy coordination, lack of policy clarity, lack of due diligence and reactionary approach to policy making by public officials. The researcher found that; engagement of ordinary citizens, removal of political connotations, policy coordination and harmonization and executive commitment can help improve national economic policy formulation in Zimbabwe.